PENGEMBANGAN SOP (STANDART OPERATING PROSEDURES) PELAPORAN GANGGUAN DENGAN METODE GAP ANALYSIS - St.Nova Meirizha; Dian Oktaviani (Fakultas Teknik UMRI, 2021)
PT.XYZ Pekanbaru sector was formed through the decision of the board of directors number 001.k/023/DIR/1996 dated February 7, 1996. It can be seen that one of PT.PLN's service activities is receiving reports of disturbances from service units. In reporting the disturbances received by the Operations and Maintenance Department (OPHAR), there were still several problems with disturbances from each service unit (UL), namely (ULPTG) Teluk Lembu, (PLTA) Koto Panjang, and (PLTG/MG) Duri, in reporting disturbance, the information provided is not detailed so that the information received is not in accordance with the needs of the operation and selection department, there is no schedule for sending disturbance reports, disturbance reports are past schedule when there is a disturbance and long delivery times, and there is no evaluation report and recommendation report from the unit. services as well as the absence of a chronology of disturbance validation reports. By conducting a gap analysis, we will compare the current conditions with the ideal conditions expected by the OPHAR department regarding the current SOP for reporting disturbances. From the results of the gap analysis, it can be concluded that there are 2 (two) SOP procedures that have gaps because they are not in accordance with the company's EAM standards.